Manejo da adubação na cultura do feijão em sistema orgânico de produção - Pereira, Leandro Barradas [UNESP] (2014)
Food production systems currently tend to more sustainable management. One of the main barriers to common bean organic farming is the manure management. The aim of this study was to evaluate the influence of organic fertilizer doses on base of bovine waste, method and time of application, on the components of production and productivity, verifying their technical and economic feasibility on common bean crop in irrigated organic system. The experimental design was a randomized block in a factorial scheme 4x2x2 with 16 treatments and 4 replications, with doses of: 1.0; 1.5; 2.0 and 2.5 t ha 1 , two application time: 30 days before and at day of sowing, and two methods of application: spread and incorporated and at planting furrow. The experiment was conducted in the Andradina (SP) countyfor the years 2011 and 2012 in a red Latosol, being irrigated by sprinkler. The common bean was sowed mechanically in the days 05/31/2011 and 06/14/2012, using the IAC Alvorada in spacing of 0.50 m between rows and twelve seeds per meter. In both years, the management sidedressing was performed 30 days after sowing and the application of 1,670 kg ha -1 of powder organic fertilizer NPK, corresponding to 50 kg ha -1 of N. It was concluded that the methods and time of application of the organic fertilizer did not affect the yield components and grain yield; the dose of 2.5 t ha -1 of organic fertilizer led to higher grain yield in 2012, but did not express its maximum productivity capacity; the best economic returns were obtained with doses of 1.5 t ha -1 and 2.5 t ha -1 of organic fertilizer in crop years 2011 and 2012, respectively